Determinasi Energi Metabolis dan Kandungan Nutrisi Hasil Samping Pasar Sebagai Potensi Bahan Pakan Lokal Ternak Unggas - Sugiyono Sugiyono; Novita Hindratiningrum; Yuni Primandini (Jurnal Agripet, 2015)
(Determination of metabolic energy and nutrient market by product for local poultry feed ingredients)ABSTRACT. This study aims to examine the metabolic energy (ME) and proximate analysis of the coconut husk, garlic skin, heart of young jackfruit, in order to see its potential as a local feed ingredients for poultry, especially chicken. The study was conducted in 3 stages include feed preparation stage, treatment stage and retrieval of data. Stage of treatment involves measurement of metabolic energy to "force feeding" the appropriate method of Sibbald (1976). The results of the proximate analysis and gross energy (GE) are water content ranged from 6.28 to 13.60%, from 5.09 to 12.34% crude protein, crude fat from 0.57 to 48.72%, crude fiber 31.33 to 51.66 %, from 2.38 to 8.39% ash, extract materials without nitrogen from 3.19 to 27.11% and GE 3387.21 to 6491.17 (kcal/kg). The results of ME research is mathematical and biological ME each feed ingredient is coconut husk 4492.84 kcal/kg; 4025.59 kcal /kg, the heart of young jackfruit 1533.44 kcal/kg ; 1625.39 kcal/kg , garlic skins 1388.76 kcal/kg; 1327.65 kcal/kg, leather bean sprouts in 1392.48 kcal/kg; 1089 .33 kcal/kg . Conclusion The study is based on the results of the proximate analysis, the content of GE and EM biological byproduct feedstuffs markets that have potential for use in poultry rations are coconut husk being able to supply the highest energy.